Solid electrolyte, its manufacturing method and electrochemical cell
A solid electrolyte with a double perovskite-type crystal structure, specifically designed for proton conductive ceramic fuel cells, addresses the challenges of chemical instability, sinterability, and proton conductivity, resulting in enhanced performance and reliability of the fuel cells.
Patent Information
- Application Number
- JP2020131239
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-31
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-07-31
AI Technical Summary
Existing solid electrolytes for proton conductive ceramic fuel cells (PCFCs) face challenges with chemical instability, sinterability, and proton conductivity, which affect the long-term reliability and performance of the fuel cells.
A solid electrolyte with the composition A2B1 1-x M1 x B2 1-y M2 y O6, where A is an alkaline earth metal, B1 includes rare earth elements, B2 are transition metals, M1 and M2 are specific elements, and x and y are within certain ranges, is developed. This electrolyte has a double perovskite-type crystal structure, which enhances chemical stability and sinterability, and achieves high proton conductivity.
The developed solid electrolyte exhibits excellent proton conductivity, sinterability, and chemical stability, leading to improved performance and long-term reliability of PCFCs, making them suitable for next-generation energy supply systems.
Smart Images

Figure 0007659717000001 
Figure 0007659717000002 
Figure 0007659717000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolyte, a method for producing the same, and an electrochemical cell. [Background technology]
[0002] In recent years, solid oxide fuel cells (SOFCs) and proton conductive ceramic fuel cells (PCFCs), which have high energy conversion efficiency, have been attracting attention as next-generation energy supply systems.
[0003] SOFCs use a solid electrolyte with ion conductivity (oxide ion conductivity) as the electrolyte, and are constructed by joining a fuel electrode (anode) to one surface of the electrolyte layer and an air electrode (cathode) to the other surface. When fuel containing hydrogen is supplied to the anode and oxygen (air) to the cathode, electrical energy can be extracted through the following electrochemical reaction. Anode reaction: 2H2+2O 2- → 2H2O+4e - (Response 1) Cathodic reaction: O2 + 4e - → 2O 2- (Response 2) Total reaction: 2H2+O2→2H2O
[0004] On the other hand, PCFCs use a solid electrolyte with proton conductivity (hydrogen ion conductivity) as the electrolyte, and are constructed by joining a fuel electrode (anode) to one surface of the electrolyte layer and an air electrode (cathode) to the other surface. When a hydrogen-containing fuel (fuel gas) is supplied to the anode and oxygen (air) to the cathode, electrical energy can be extracted through the following electrochemical reaction. Anode reaction: 2H2 → 4H + +4e - (Reaction 3) Cathodic reaction: 4H + +O2+4e - → 2H2O (reaction 4) Total reaction: 2H2+O2→2H2O
[0005] The solid electrolyte that forms the electrolyte layer of a PCFC is required to have proton conductivity (hydrogen ion conductivity). Known solid electrolytes with proton conductivity include BaCeO3 and BaZrO3 compounds (oxides) with a perovskite structure. These compounds have traditionally been made of sintered bodies made by sintering oxides.
[0006] In order to improve the performance of PCFCs, further research is being conducted into solid electrolyte materials. In particular, solid electrolytes for PCFCs that have improved proton conductivity, good sintering properties, and chemical stability are required.
[0007] Specifically, BaCeO3-based oxides with a perovskite structure were chemically unstable. When a PCFC is formed, chemical instability reduces the long-term reliability of the PCFC. On the other hand, BaZrO3-based oxides are compounds that are difficult to sinter, making densification difficult. When densification becomes difficult, substances other than protons (e.g. atomic ions and gas molecules) begin to permeate the solid electrolyte (electrolyte layer). Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a solid electrolyte having high proton conductivity and excellent sinterability and chemical stability, a method for producing the same, and an electrochemical cell. [Means for solving the problem]
[0009] The solid electrolyte of the present invention that solves the above problems is A2B 1 1-x M 1 x B 2 1-y M 2 y O6 (A: alkaline earth metal, B 1 At least one selected from La, Nd, Gd, Ce, Pr, and Yb; B 2: At least one selected from transition metals, M 1 At least one selected from Be, Mg, Ca, and Sr; M 2 : at least one selected from Ta, Sb, Zr, Sn, Ti, and Mg, 0≦x≦0.30, 0≦y≦0.30).
[0010] The method for producing a solid electrolyte of the present invention, which solves the above problems, is characterized by comprising the steps of: mixing raw material powders weighed to have a predetermined atomic ratio; heat-treating the mixture at a temperature below the sintering temperature to produce a precursor; and heat-treating the precursor at a temperature equal to or higher than the sintering temperature.
[0011] The electrochemical cell of the present invention, which solves the above problems, is characterized by using the solid electrolyte as defined in any one of claims 1 and 2. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a diagram showing a double perovskite crystal structure. [Diagram 2] FIG. 1 is a diagram showing a perovskite crystal structure. [Diagram 3] 1 is a flowchart showing steps of a method for producing a solid electrolyte according to an embodiment. [Figure 4] FIG. 2 is a diagram showing the results of XRD measurement in Examples 1 and 2. [Diagram 5] FIG. 2 is a diagram showing the results of XRD measurement in Examples 3 to 5. [Figure 6] FIG. 13 is a diagram showing the results of XRD measurement in Example 6. [Figure 7] FIG. 2 is a diagram showing the measurement results of proton conductivity in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below using embodiments. Note that the present invention is not limited to the configurations shown in the embodiments, and includes configurations that are arbitrarily modified without departing from the gist of the present invention.
[0014] [Solid electrolyte] The solid electrolyte in this form is A2B 1 1-x M 1 x B 2 1-y M 2 y O6 (A: alkaline earth metal, B 1 At least one selected from La, Nd, Gd, Ce, Pr, and Yb; B 2 : At least one selected from transition metals, M 1 At least one selected from Be, Mg, Ca, and Sr; M 2 : at least one selected from Ta, Sb, Zr, Sn, Ti, and Mg, 0≦x≦0.30, 0≦y≦0.30).
[0015] The solid electrolyte of this embodiment is B having the above composition. 1 and B. 2 The valence of M 1 and M 2 When the valence satisfies this relationship, the solid electrolyte of the present embodiment has suitable proton conductivity. 1 and B 2 The valences of M may be the same or different, but are preferably the same. 1 and M. 2 The valences of M may be the same or different. 1 and M. 2 If the valences of are different, B 1 and B 2 All of the valences of M 1 and M. 2 It is preferable that the valence of the aryl group is smaller than the smaller valence of the aryl group.
[0016] In the solid electrolyte of the present embodiment, A in the above composition is preferably Ba. 1 and B 2The elements may be the same or different. In the above composition, the solid electrolyte of the present embodiment has a double perovskite crystal structure as described below when 0≦x≦0.30 and 0≦y≦0.30. When x and y exceed 0.30, two crystal phases are likely to occur, and the proton conductivity (proton conductivity value) is likely to decrease. It is more preferable that 0≦x≦0.25 and 0≦y≦0.25, and further more preferable that 0≦x≦0.20 and 0≦y≦0.20.
[0017] The compound of the solid electrolyte of this embodiment is an oxide having a crystal structure called a double perovskite type. The double perovskite type oxide is an oxide having suitable proton conductivity (ionic conductivity). Here, having suitable proton conductivity means that the proton conductivity is 10 -5 S / cm or more, preferably 10 -3 S / cm or more. In other words, when an electrochemical cell (for example, a fuel cell) is formed, the material exhibits high proton conductivity at the operating temperature at which the desired cell characteristics can be exhibited.
[0018] The double perovskite crystal has the crystal structure shown in Figure 1. Figure 1 is a diagram showing the crystal structure of a double perovskite compound represented by the general formula: A2MM'O6 (A: Ba, M: Nd or Gd, M': Nb). On the other hand, a perovskite-type crystal has a crystal structure shown in Figure 2. Figure 2 is a diagram showing the structure of a perovskite-type compound represented by the general formula: AMO3 (A: Ba, M: Zr or Ce).
[0019] As shown in Figure 1, the double perovskite compound is composed of M' (pentavalent atomic ion, Nb 5+ ) and the oxygen octahedron surrounding M (a trivalent atomic ion, M 3+ ) and the oxygen octahedron surrounding A(Ba 2+ ) The space group of this structure is Fm-3m (No. 225). In contrast, as shown in Figure 2, perovskite-type compounds contain M (tetravalent atomic ions, M 4+ ) is surrounded by an oxygen octahedron, A(Ba 2+ ) The space group of this structure is Pm-3m (No. 221).
[0020] As is clear from Figures 1 and 2, the symmetry of the crystal structure is obviously different between the double perovskite type compound and the perovskite type compound. Due to this difference in crystal structure, the double perovskite type compound has higher chemical stability than the perovskite type compound. Double perovskite type compounds have multiple oxygen octahedra surrounding elements with different valences, and the distance between the oxygen octahedra surrounding the bulky elements is long. This makes it easier for atoms to move within the solid electrolyte. In other words, sintering reactions involving the movement of atoms are more likely to occur. In other words, they have high sinterability.
[0021] The compound of the solid electrolyte of this embodiment is Ba2B 1 1-x Ca x In the above composition formula, A is Ba, B is NbO6. 2 :Nb, M 1 :Ca, y = 0. This compound has the crystal structure shown in Figure 1 in which part of M (trivalent) is replaced with Ca (divalent). The solid electrolyte of the present embodiment preferably has an oxygen-deficient crystal structure, which allows the solid electrolyte of the present embodiment to have higher proton conductivity.
[0022] (Effects of this form) The solid electrolyte of the present embodiment is a compound having the above-mentioned composition, and is made of an oxide having suitable proton conductivity (ion conductivity). This oxide has excellent sinterability and chemical stability, and the solid oxide of the present embodiment also has excellent sinterability and chemical stability.
[0023] The solid electrolyte of the present embodiment is not limited in its manufacturing method, and can be manufactured, for example, by the following manufacturing method. [Method of manufacturing solid electrolyte] The method for producing the solid electrolyte of this embodiment includes the steps shown in FIG. (Raw material weighing process: S1) The raw material weighing step is a step of weighing the raw material powder of the solid electrolyte. Specifically, it is a step of weighing the raw material powder of the solid electrolyte in a ratio that allows the solid electrolyte to be produced. The raw material powder of the solid electrolyte is a weight ratio of inorganic elements (A, B) that constitute the solid electrolyte. 1 ,M 1 ,B 2 ,M 2 Powders of compounds (powder of oxides or carbides) containing the above elements can be used. Salt compounds of inorganic elements such as carbonates can also be used. Furthermore, the raw material for the solid electrolyte can be either a compound containing one type of inorganic element constituting the solid electrolyte or a compound containing two or more types.
[0024] The raw powder of the solid electrolyte is weighed so that the inorganic elements have a predetermined atomic ratio (atomic ratio of the solid electrolyte after production). Note that a part of the inorganic elements may evaporate during the sintering process, causing a change in the atomic ratio. In this case, it is preferable to weigh the raw powder of the inorganic element that is evaporated at an atomic ratio including the amount of evaporation. In other words, it is preferable to weigh the raw powder of the inorganic element in an amount larger than the predetermined atomic ratio by the amount of evaporation.
[0025] (Mixing process: S2) The mixing step is a step of mixing the weighed raw material powders. The mixing step is a step of mixing the raw material powders to obtain a uniformly mixed raw material powder. The method of mixing the raw material powders is not limited as long as each raw material powder can be mixed in a uniformly dispersed state. For example, a method of mixing using a mixing device such as a ball mill, a planetary ball mill, or a tromill can be mentioned. The mixing step may be performed by either a dry mixing method in which raw material powders are mixed in a dry state or a wet mixing method in which raw material powders are mixed in a state of being dispersed in a solvent or the like.
[0026] (Drying process: S3) The drying process is a process for drying the mixed raw material powders. The drying process is not limited to a specific drying method as long as it can dry the mixed powders. The drying process removes moisture contained in the mixed powders (moisture adsorbed on the surfaces of the raw material powder particles). Furthermore, when wet mixing is performed in the mixing process, a dispersion medium such as a solvent is removed. The method for drying the mixed powder is not limited. The drying step is, for example, a step of heating the mixed powder at a temperature higher than room temperature. Preferably, the drying step is a step of heating at a temperature at which the moisture (and dispersion medium) in the mixed powder evaporates. The heating temperature is not limited, and a temperature of 50° C. or higher is preferable. A temperature of 100° C. or higher is more preferable. The pressure during heating is also not limited, and normal pressure or reduced pressure is preferable.
[0027] (Pre-firing process: S4) The calcination process is a process in which the dried raw material powder (mixed powder) is heat-treated at a temperature below the sintering temperature. In the calcination process, the raw material powder (mixed powder) is heat-treated to promote a reaction (atomic diffusion reaction) between the inorganic elements in each raw material powder. As the reaction between the inorganic elements progresses, a precursor (a compound whose overall composition has the composition of a solid electrolyte. It has a crystal structure in which the raw material powders are mixed, and has a different crystal structure from that of the final product) is generated. In other words, the calcination process is a process in which a precursor is generated by heat-treating at a temperature below the sintering temperature. Here, the sintering temperature is the lowest temperature among the temperatures at which the reaction progresses in the sintering process described below.
[0028] The heat treatment in the calcination step may be performed at a temperature lower than the sintering temperature and capable of producing a precursor, for example, at a temperature 100 to 300° C. lower than the sintering temperature. The pressure during the heat treatment in the calcination step is not limited, but is preferably normal pressure or reduced pressure. The treatment time for the heat treatment in the calcination step is not limited either, but may be the time required for the reaction to produce the precursor to be completed.
[0029] (Crushing process: S5) The pulverization step is a step of pulverizing the precursor. In the pulverization step, the precursor produced by the calcination is pulverized to produce a precursor powder. The particle size (average particle size: D50) of the precursor powder is not limited. In the pulverization step, the specific method for pulverizing the precursor is not limited. For example, the precursor is physically pulverized using an apparatus such as a ball mill, a planetary ball mill, or a tromill to obtain a precursor powder.
[0030] (Molding process: S6) The forming step is a step of forming the precursor powder obtained in the pulverization step into a predetermined shape. The predetermined shape is the shape when the solid electrolyte of this embodiment is used (i.e., the shape corresponding to the electrolyte layer in the electrochemical cell described later), and examples of the shape include a plate-like or sheet-like thin plate shape. Note that, when a volume change (specifically, shrinkage) occurs during the sintering step, the predetermined shape is a shape that assumes the volume change.
[0031] The molding step is preferably a step of compression molding the precursor powder. When the precursor powder is compression molded, the molding conditions such as the pressure, the pressing time, and the pressing temperature are not limited. For example, molding methods such as die molding, which uses a mold having a cavity corresponding to a predetermined shape for pressure molding, and die molding, which uses an isostatic pressure method such as HIP molding or CIP molding, can be used.
[0032] (Sintering process: S7) The sintering step is a step of heat-treating the precursor molded body at a temperature equal to or higher than the sintering temperature. In the sintering step, the precursor molded body is heat-treated to sinter the precursor. When the precursor is sintered, an exchange reaction of the precursor elements proceeds, and a reaction to generate a compound having a double perovskite crystal structure proceeds, and a compound of the solid electrolyte of this embodiment is generated. Here, the sintering temperature is the temperature at which the precursor is sintered, and is the lowest temperature among the temperatures at which the exchange reaction of the precursor elements proceeds, and the reaction to generate a compound having a double perovskite crystal structure proceeds to generate a compound of the solid electrolyte. Even if the heat treatment temperature is lower than the sintering temperature, an exchange reaction of the precursor elements may occur, but the reaction to generate a compound having a double perovskite crystal structure does not proceed. In the sintering step, a sintering reaction between particles of the precursor powder progresses, and a solid electrolyte compound having a predetermined shape can be obtained. More specifically, a solid electrolyte made of a compound having the above composition (a compound having a double perovskite crystal structure) is produced. That is, a solid electrolyte having a thin plate shape such as a plate or sheet shape can be obtained by molding in the molding step.
[0033] In the sintering step, the precursor compact is heat-treated under treatment conditions that allow the sintering reaction to proceed. The conditions for the heat treatment are not limited. That is, the heat treatment conditions, such as the heat treatment temperature, heat treatment time, and atmosphere, are not limited. The heat treatment temperature may be a temperature at which the exchange reaction of the precursor elements proceeds and at which the reaction that produces a compound having a double perovskite crystal structure proceeds (i.e., a temperature equal to or higher than the sintering temperature). The heat treatment time may be a time at which the reaction that produces a solid electrolyte compound is completed. The atmosphere may be an atmosphere in which the reaction that produces a solid electrolyte compound can proceed. It is preferable that the atmosphere is air to oxygen atmosphere (i.e., the heat treatment at a temperature equal to or higher than the sintering temperature is performed in an oxygen-containing atmosphere). The solid electrolyte of the present embodiment is produced by carrying out these steps (S1 to S7). Regarding the conditions other than those mentioned above, conventionally known methods (steps) can be appropriately used. For example, after the sintering step, a step of polishing and shaping the surface may be carried out, which improves the dimensional accuracy and exposes a clean surface of the solid electrolyte compound.
[0034] (Effects of this form) According to the method for producing a solid electrolyte of the present embodiment, the above-mentioned solid electrolyte of the present embodiment, i.e., a solid electrolyte made of a compound having the above-mentioned composition, can be produced. In other words, the method for producing a solid electrolyte of the present embodiment exhibits the effect of being able to produce a solid electrolyte having suitable proton conductivity, as well as excellent sinterability and chemical stability.
[0035] [Electrochemical cell] The solid electrolyte of the present embodiment has proton conductivity and can be used in components that require this property, for example, as an electrolyte (solid electrolyte) for electrochemical cells. An electrochemical cell refers to a battery cell (or a battery) that extracts electric power from the chemical energy of fuel through an electrochemical reaction. An example of an electrochemical cell is a battery cell of a fuel cell. The solid electrolyte of the present embodiment is preferably a solid electrolyte of a fuel cell.
[0036] [Fuel cell] The structure of the fuel cell (fuel cell) using the solid electrolyte of this embodiment is not limited. The fuel cell may have the same structure as that of a conventionally known proton conductive ceramic fuel cell (PCFC). The structure of the fuel cell not specifically mentioned may be a conventionally known structure. The fuel cell may have, for example, an electrolyte layer, a fuel electrode, and an air electrode. The electrolyte layer is made of the solid electrolyte of the present embodiment. The electrolyte layer is made of the solid electrolyte formed in a plate shape. The fuel electrode is formed on one surface of a plate-shaped electrolyte layer. The fuel electrode is an electrode to which a fuel (fuel gas) containing hydrogen is supplied. The fuel electrode has an electrode body that is integrally provided on one surface of the electrolyte layer. This electrode body is in the form of a foil (mesh) with many holes that allow the passage of the gas (fuel gas) containing hydrogen. In the fuel electrode, the fuel gas passes through the many holes in the electrode body, and hydrogen comes into contact with one surface of the electrolyte layer, causing an electrode reaction. Electrons generated in the electrode reaction flow from the electrode body to an external element. That is, the above reaction 3 occurs. The air electrode is formed on the other surface of the plate-like electrolyte layer. The air electrode is an electrode to which oxygen-containing gas (air) is supplied. The air electrode has a catalyst and an electrode body that are integrally provided on the other surface of the electrolyte layer. This electrode body is in the form of a foil (mesh) with many holes that allow the gas to pass through. In the air electrode, the oxygen-containing gas (air) passes through the many holes in the electrode body, and the oxygen comes into contact with the other surface of the electrolyte layer and reacts. The electrons consumed in the electrode reaction flow from the external element through the electrode body. In other words, the above reaction 4 occurs.
[0037] The fuel cell may further have a configuration in which the electrolyte layer is sandwiched between a fuel electrode separator and an air electrode separator. The fuel electrode separator has a plurality of fuel gas flow paths, and the air electrode separator has a plurality of oxygen-containing gas flow paths. The cross-sectional shapes of the flow paths (fuel gas flow paths, oxygen-containing gas flow paths) formed on the surfaces of the fuel electrode separator and the air electrode separator facing the electrolyte layer are not limited. The fuel cell may have a configuration in which a plurality of fuel cells are stacked.
[0038] (Effects of this form) The electrochemical cell of the present embodiment is characterized in that it uses the solid electrolyte of the present embodiment in an electrolyte layer, that is, it uses the solid electrolyte having the above-mentioned effects, and exerts the above-mentioned effects (especially the effect of a long life). EXAMPLES
[0039] The present invention will be described in detail below with reference to examples. As examples, solid electrolytes are produced. Example 1 The solid electrolyte in this example is Ba2Nd 0.8 Ca 0.2 This compound is made of a compound represented by NbO6. In the above composition formula, A: Ba, B 1 :Nd, B 2 :Nb, M 1 :Ca, x=0.2, y=0.
[0040] The solid electrolyte of this example is produced by the above-mentioned production method, specifically, by carrying out the following steps. (Raw material weighing process: S1) In the raw material weighing step, BaCO3 is prepared as the Ba source, Nd2O3 is prepared as the Nd source, CaCO3 is prepared as the Ca source, and Nb2O5 is prepared as the Nb source. The powders of the prepared compounds are weighed out so that the atomic ratio of Ba:Nd:Ca:Nb is 2:0.8:0.2:1. (Mixing process: S2) The powders of the prepared compounds are mixed uniformly in a ball mill at 100 rpm for 24 hours. (Drying process: S3) The mixed raw material powder is kept at 50°C for 1 hour (under normal pressure) and dried. (Pre-firing process: S4) The dried raw material powder is charged into the firing vessel, where it is maintained in an uncompressed state. Next, the sintering container is placed in a heating furnace and heat-treated at 1300°C for 10 hours (at atmospheric pressure). This heat treatment results in the precursor oxide (a mixture of the raw material powders with an overall composition of Ba2Nd 0.8 Ca 0.2 NbO6) is produced.
[0041] (Crushing process: S5) The precursor oxide produced in the calcination step (S4) is allowed to cool, and then pulverized in a ball mill at 100 rpm for 24 hours. The precursor oxide is pulverized to have a particle size of 5 μm or less. (Molding process: S6) The obtained precursor oxide powder is molded into a disk (predetermined shape) with a diameter of 18 mm and a thickness of 1.5 mm. The precursor oxide powder is molded under a molding pressure of 98.0665 MPa (1 ton weight / cm 2 ) to press down. (Sintering process: S7) The compact is placed in a heating furnace and heat-treated at 1500°C for 10 hours (atmospheric atmosphere, normal pressure). The sintering temperature of the solid electrolyte of this example is 1500°C. A disk-shaped solid electrolyte of this example is produced by this heat treatment. The produced solid electrolyte of this example is a dense sintered body without defects such as cracks. In other words, it is a solid electrolyte that does not transmit gases such as H2 and O2.
[0042] Example 2 The solid electrolyte of this example is made of a compound represented by Ba2NdNbO6. In the above composition formula, A: Ba, B 1 :Nd, B 2 :Nb, x=0, y=0. The solid electrolyte of this example was produced in the same manner as in Example 1, except that the blend ratio of the powders of the respective compounds in the raw material weighing step (S1) was changed. The sintering temperature of the solid electrolyte of this example was 1500°C.
[0043] Example 3 The solid electrolyte in this example is Ba2Gd 0.7 Ca 0.3 This compound is made of a compound represented by NbO6. In the above composition formula, A: Ba, B 1 : Gd, B 2 :Nb, M 1 :Ca, x=0.3, y=0. The solid electrolyte of this example was produced in the same manner as in Example 1. The differences from Example 1 are as follows. In the raw material weighing step (S1), Gd2O3 was used as the Gd source. In the calcination step (S4), the mixture is heat-treated at 1350° C. for 10 hours (at atmospheric pressure). This heat treatment produces a precursor oxide (a mixture of raw material powders with an overall composition of Ba2Gd 0.7 Ca 0.3NbO6) is produced. In the sintering step (S7), the heat treatment is performed under the conditions of 1600°C x 10 hours (air atmosphere, normal pressure). The sintering temperature of the solid electrolyte in this example is 1600°C.
[0044] Example 4 The solid electrolyte in this example is Ba2Gd 0.8 Ca 0.2 This compound is made of a compound represented by NbO6. In the above composition formula, A: Ba, B 1 : Gd, B 2 :Nb, M 1 :Ca, x=0.2, y=0. The solid electrolyte of this example was produced in the same manner as in Example 3, except that the blend ratio of the powders of the respective compounds in the raw material weighing step (S1) was changed. The sintering temperature of the solid electrolyte of this example was 1600°C.
[0045] Example 5 The solid electrolyte of this example is made of a compound represented by Ba2GdNbO6. In the above composition formula, A: Ba, B 1 : Gd, B 2 :Nb, x=0, y=0. The solid electrolyte of this example was produced in the same manner as in Example 3, except that the blend ratio of the powders of the respective compounds in the raw material weighing step (S1) was changed. The sintering temperature of the solid electrolyte of this example was 1600°C.
[0046] Example 6 The solid electrolyte in this example is Ba2La 0.9 Ca 0.1 This compound is made of a compound represented by NbO6. In the above composition formula, A: Ba, B 1 :La, B 2 :Nb, M 1 :Ca, x=0.1, y=0. The solid electrolyte of this example was produced in the same manner as in Example 1. The differences from Example 1 are as follows. In the raw material weighing step (S1), La2O3 was used as the La source. In the calcination step (S4), heat treatment is performed under the condition of 1350°C x 10 hours (at normal pressure). By this heat treatment, the precursor oxide (the raw material powder is mixed and the overall composition is Ba2La 0.9 Ca 0.1 NbO6) is produced. In the sintering step (S7), the heat treatment is performed under the conditions of 1600°C x 10 hours (air atmosphere, normal pressure). The sintering temperature of the solid electrolyte in this example is 1600°C.
[0047] Comparative Example 1 The solid electrolyte in this example is BaZr 0.95 Y 0.05 The solid electrolyte of this example is composed of a compound represented by the formula O3. The solid electrolyte of this example differs from those of the other examples in the composition and crystal structure of the compound. The compound of this example has a perovskite-type crystal structure. The solid electrolyte of this example was produced in the same manner as in Example 1. The differences from Example 1 are as follows. In the raw material weighing step (S1), BaCO3 was used as the Ba source, ZrO2 was used as the Zr source, and Y2O3 was used as the Y source. The powders of the prepared compounds were weighed so that the atomic ratio of Ba:Zr:Y was 1:0.95:0.05. In the calcination step (S4), the mixture is heat-treated at 1400° C. for 10 hours (at atmospheric pressure). This heat treatment results in a precursor oxide (a mixture of raw material powders with an overall composition of BaZr 0.95 Y 0.05 O3) is produced. In the sintering step (S7), heat treatment is performed under the conditions of 1600° C.×10 hours (air atmosphere, normal pressure).
[0048] Comparative Example 2 The solid electrolyte in this example is BaCe 0.9 Nd 0.1 The solid electrolyte of this example is composed of a compound represented by the formula O3. The solid electrolyte of this example differs from those of the other examples in the composition and crystal structure of the compound. The compound of this example has a perovskite-type crystal structure. The solid electrolyte of this example was produced in the same manner as in Example 1. The differences from Example 1 are as follows. In the raw material weighing step (S1), BaCO3 was used as the Ba source, CeO2 was used as the Ce source, and Nd2O3 was used as the Nd source. The powders of the prepared compounds were weighed so that the atomic ratio of Ba:Ce:Nd was 1:0.9:0.1. In the calcination step (S4), the mixture is heat-treated at 1400° C. for 10 hours (at atmospheric pressure). This heat treatment produces a precursor oxide (a mixture of raw material powders with an overall composition of BaCe 0.9 Nd 0.1 O3) is produced. In the sintering step (S7), heat treatment is performed under the conditions of 1600° C.×10 hours (air atmosphere, normal pressure).
[0049] [evaluation] The solid electrolytes of the above examples were evaluated by measuring the XRD diffraction pattern and the proton conductivity.
[0050] [XRD] The XRD of the solid electrolyte of each Example was measured, and the measurement results of Examples 1 and 2 are shown in FIG. 4, and the measurement results of Examples 3 to 5 are shown in FIG. 4 and 5, when Example 1 is compared with Example 2, it can be seen that in the solid electrolyte of Example 1, part of the Nd in the solid electrolyte of Example 2 is partially substituted with Ca. When Examples 3 and 4 are compared with Example 5, it can be seen that in the solid electrolyte of Examples 3 and 4, part of the Gd in the solid electrolyte of Example 5 is partially substituted with Ca.
[0051] That is, Ba2B 1 1-x Ca x NbO6(B 1 The solid electrolytes of Examples 1 to 5 are Nd or Gd, 0≦x≦0.30), 1 It is found that the substitution of Ca partially results in oxygen deficiency (having an oxygen-deficient crystal structure), resulting in high proton conductivity. Moreover, it can be confirmed that the solid electrolytes of Examples 1 to 5 have a double perovskite crystal structure from the XRD diffraction patterns of Figures 4 and 5. By having a double perovskite crystal structure, the solid electrolytes of Examples 1 to 5 have high chemical stability. Furthermore, by having a double perovskite crystal structure, the solid electrolytes of Examples 1 to 5 also have excellent sinterability. In addition, the XRD diffraction patterns of the solid electrolytes of Examples 1 to 5 show sharp peaks as shown in Figures 4 and 5. That is, the solid electrolytes of Examples 1 to 5 have high crystallinity. The solid electrolytes of Examples 1 to 5 are made of sintered bodies without defects and have excellent sinterability.
[0052] [XRD] The solid electrolyte of Example 6 was subjected to XRD measurement, and the measurement results are shown in FIG. The XRD diffraction pattern in FIG. 6 has peaks similar to those in the XRD diffraction patterns in FIG. 4 and FIG. 5. That is, it can be confirmed that the solid electrolyte of Example 6 has a double perovskite crystal structure, similar to the solid electrolytes of Examples 1 to 5. Therefore, the solid electrolyte of Example 6 has high chemical stability, similar to the solid electrolytes of Examples 1 to 5. Furthermore, since the solid electrolyte of Example 6 has a double perovskite crystal structure, it also has excellent sinterability. The XRD diffraction pattern of the solid electrolyte of Example 6 also shows a sharp peak. In other words, the solid electrolyte of Example 6 also has high crystallinity like Examples 1 to 5, and is excellent in sinterability.
[0053] [Proton conductivity] To evaluate Examples 1 and 4, the proton conductivity was measured by an AC impedance method, and the measurement results are shown in Fig. 7. Fig. 7 also shows the proton conductivity (literature value) of Comparative Examples 1 and 2. 7, the solid electrolytes of Examples 1 and 4 have higher proton conductivity than the solid electrolytes of Comparative Examples 1 and 2. In other words, the compound having a double perovskite crystal structure has better proton conductivity than the compound having a perovskite crystal structure. As described above, the solid electrolytes of the Examples have superior proton conductivity compared to the solid electrolytes of the Comparative Examples.
[0054] As described above in detail, the solid electrolytes of the Examples have superior proton conductivity compared to the Comparative Examples, and the solid electrolytes of the Examples have superior sinterability and chemical stability due to their crystal structures. As a result, electrochemical cells (fuel cells) using these solid electrolytes exhibit the effect of being excellent in performance and having a long life. Furthermore, according to the manufacturing method of the present invention, a solid electrolyte exhibiting these effects can be manufactured.
Claims
1. Ba 2 N.D. 0.8 Ca 0.2 NbO 6 , Ba 2 NdNbO 6 , Ba 2 G.D. 0.7 Ca 0.3 NbO 6 , Ba 2 G.D. 0.8 Ca 0.2 NbO 6 , Ba 2 GdNbO 6 , or Ba 2 La 0.9 Ca 0.1 NbO 6 A solid electrolyte comprising at least one compound selected from the group consisting of:
2. 2. The solid electrolyte according to claim 1, which has an oxygen-deficient crystal structure.
3. Ba 2 N.D. 0.8 Ca 0.2 NbO 6 , Ba 2 NdNbO 6 , Ba 2 G.D. 0.7 Ca 0.3 NbO 6 , Ba 2 G.D. 0.8 Ca 0.2 NbO 6 , Ba 2 GdNbO 6 , or Ba 2 La 0.9 Ca 0.1 NbO 6 A method for producing a solid electrolyte which is at least one compound selected from the group consisting of A step of mixing raw material powders weighed to have a predetermined atomic ratio and heat treating the mixture at a temperature lower than the sintering temperature to generate a precursor; heat treating the precursor at a temperature equal to or greater than the sintering temperature; 2. A method for producing a solid electrolyte comprising the steps of:
4. 4. The method for producing a solid electrolyte according to claim 3, wherein the heat treatment at a temperature equal to or higher than the sintering temperature is carried out in an oxygen-containing atmosphere.
5. 3. An electrochemical cell comprising the solid electrolyte according to claim 1.
6. 6. The electrochemical cell of claim 5 which is a fuel cell.
7. 7. The electrochemical cell in accordance with claim 6, further comprising: an electrolyte layer made of said solid electrolyte; a fuel electrode provided on one surface of said electrolyte layer; and an air electrode provided on the other surface of said electrolyte layer.
Citation Information
Patent Citations
Mixed ion conductor and device using the same
JP2000302550A
Ionic conductor
JP2001307546A
Chemically Stable Proton Conducting Doped BaCeO3
US20170149082A1